Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.3 - Adding and Subtracting Rational Expressions with the Same Denominator and Least Common Denominator - Exercise Set: 25

Answer

LCD=(2)(3)(x+1)(x+1)=6$(x+1)^{2}$

Work Step by Step

$\frac{1}{3x+3}$, $\frac{8}{2x^{2}+4x+2}$ 2$x^{2}$+4x+2=2$x^{2}$+2x+2x+2=2x(x+1)+2(x+1)= =(2x+2)(x+1)=2(x+1)(x+1) 3x+3=3(x+1) LCD=(2)(3)(x+1)(x+1)=6$(x+1)^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.